2016
DOI: 10.14569/ijacsa.2016.070928
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Acoustic Features of Hypernasality and it’s Assessment

Abstract: Abstract-Hypernasality (HP) is observed across voiced phonemes uttered by Cleft-Palate (CP) speakers with defective velopharyngeal (VP) opening. HP assessment using signal processing technique is challenging due to the variability of acoustic features across various conditions such as speakers, speaking style, speaking rate, severity of HP etc. Most of the study for hypernasality (HP) assessment is based on isolated sustained vowels under laboratory conditions. We measure the variability of acoustic features a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Given the difficulty of identifying correlates of nasalization that apply across different vowels, studies often select the vowel /i/ for analysis (Haque, Ali, & Haque, 2016; Kataoka, Michi, Okabe, Miura, & Yoshida, 1996; A. S. Y. Lee, Ciocca, & Whitehill, 2003).…”
Section: 0 Sources Of Error In Formant Frequency Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the difficulty of identifying correlates of nasalization that apply across different vowels, studies often select the vowel /i/ for analysis (Haque, Ali, & Haque, 2016; Kataoka, Michi, Okabe, Miura, & Yoshida, 1996; A. S. Y. Lee, Ciocca, & Whitehill, 2003).…”
Section: 0 Sources Of Error In Formant Frequency Estimationmentioning
confidence: 99%
“…The clinical relevance of VSA has been noted across a spectrum of disorders affecting communication, including: (1) children with neurogenic speech disorders (Higgins & Hodge, 2002; Hustad, Gorton, & Lee, 2010; Liu, Tsao, & Kuhl, 2005; Narasimhan, Nikitha, & Francis, 2016); (2) adults with acquired dysarthria (Bang, Min, Sohn, & Cho, 2013; S. Kim, Kim, & Ko, 2014; Turner, Tjaden, & Weismer, 1995; Weismer, Jeng, Laures, Kent, & Kent, 2001); (3) adults with Down syndrome (Bunton & Leddy, 2011), (4) individuals with hearing loss (Palethorpe & Watson, 2003); (5) individuals with hearing loss (Palethorpe & Watson, 2003); (6) adults who have undergone glossectomy (Kaipa, Robb, O’Beirne, & Allison, 2012; Whitehill, Ciocca, Chan, & Samman, 2006); (7) adults who have undergone glossectomy (Kaipa, Robb, O’Beirne, & Allison, 2012; Takatsu et al 2017; Whitehill, Ciocca, Chan, & Samman, 2006); (8) individuals undergoing treatment for oral or oropharyngeal cancer (de Bruijn et al, 2009); (9) individuals with Class III malocclusion (Xue, Lam, Whitehill, & Samman, 2011); (8) people who stutter (Blomgren, Robb, & Chen, 1998; Hirsch et al, 2008); (9) individuals with hypernasality associated with cleft palate (Haque, Ali, & Haque, 2016); and (10) individuals in psychological distress or with self-reported symptoms of depression and post-traumatic stress disorder (Scherer, Lucas, Gratch, Rizzo, & Morency, in press; Scherer, Morency, Gratch, & Pestian, 2015).…”
Section: 0 Derived Metrics and Data Displaysmentioning
confidence: 99%
“…[6][7][8][9]21 In the same sense, it is not clear if the use of other vowels would have yielded different results as some works suggest. 23 To this respect, further studies employing three repetitions of the rest of Spanish vowels must be addressed in the future. Also, the combination of traditional acoustic parameters and other new such as modulation speetrum morphological parameters 24 or complexity measurements 25 must be employed in future works.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, acoustic cues such as weakening of formants, decrease in the strength and enhanced bandwidth of F1 and F2, rise in the amplitude between F1 and F2, introduction of pole/zero pairs in the vicinity of F1 and shifts in the formant frequencies are reported for the analysis of hypernasal speech [5]. Hence, these spectral modifications in the hypernasal speech will have an impact on the articulatory dynamics while producing vowels resulting in vowel centralization and in turn affecting speech intelligibility [6].…”
Section: Introductionmentioning
confidence: 99%
“…This metric has helped speech-language pathologists to study the spectral changes, the articulatory precision and found useful in predicting speech intelligibility in various speech disorders like Down syndrome [7], cerebral palsy [8], hearing impairment [9], dysarthria [10]. A recent study on VSA on CLP speakers reported the reduced vowel space in their speech [6]. However, the effect of severity of hypernasality on vowel space was not explicitly studied in the literature.…”
Section: Introductionmentioning
confidence: 99%